Исследование влияния повреждений зубчатых передач на параметры их вибраций - Гаврилов, Сергей Алексеевич; Ишин, Николай Николаевич; Гоман, Аркадий Михайлович; Скороходов, Андрей Станиславович; Дакало, Юрий Александрович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Для эффективной вибродиагностики необходимы достоверные критерии в виде предельно допустимых уровней параметров вибраций, по которым производится оценка состояния механизма. Одним из объективных параметров нормирования вибрации зубчатых механизмов могут служить величины виброускорения и виброскорости. Приведены результаты экспериментальных исследований влияния локального повреждения зуба шестерни и эксплуатационных условий работы на параметры вибраций элементов трехступенчатого цилиндрического редуктора. Предметом анализа и обработки являются спектральные характеристики вибрационного сигнала, имеющие высокую чувствительность к изменению состояния зубчатых колес. Показано, что при разработке методик оценки и прогнозирования остаточного ресурса приводов при переходе от системы планово-предупредительных ремонтов к обслуживанию по фактическому состоянию, необходимо учитывать некоторые особенности проявления повреждений в вибросигналах, позволяющие получить дополнительные косвенные диагностические параметры для анализа.

Vibration diagnostics are widely used to monitor the state of gear drives and assess their life. Effective vibration diagnostics require reliable criteriain the form of maximum permissible levels of vibrationparameters against which the condition of the mechanism is assessed. Vibration acceleration and vibration speed values can be one of objective parameters of vibration regulation of gear mechanisms. The results of experimental studies of the defect of gear tooth damage and operating conditions on the vibration parameters of the elements of a three-stage cylindrical gearbox are presented. The subject of analysis and processing are spectral characteristics of vibration signal, having high sensitivity to change of gear wheels state. It has been established that with the development of local defect vibration parameters change not only for damagedgear, but also for technically serviceable gears. The tests showed that when developing methods for estimating and predicting the residual life of drives during the transition from a preventive main-tenance to condiction based manitenance, it is necessary to take into account some features of the manifestation of damage in vibration signals, which allow obtaining additional indirect diagnostic parameters for analysis.
Study of impact of gear train damages on parameters of their vibrations
Keywords: локальное повреждение; спектр; зубцовая частота; local damage; spectrum; tooth frequency